Conditions over the equatorial area during the period of monsoon experiment (Monex) 1973 - DESAI, B. N.; RANGACHARI, N.; SUBRAMANIAN, S. K.; SAMBAMOORTHY, T. M. (MAUSAM, 1976)
The surface and upper air observations recorded by the two Russian ships, viz., Okean (EREI) and Voekov (UAAX) at different locations over the equator and by the observatories over Kenya during the monsoon experiment 1973, have been examined in detail to get an idea about the conditions over the equator during southwest monsoon. Comparative study of the observations over the equator, at Long. 60° and 50°E and of observations recorded at Garissa and Nairobi during the period 27 May to 4 June and 24 June to 2 July, has been made and presented in this paper. The observations of the ship Okean over the equator on its cruise from about Long 45.0°E to 70.0°E during the period from 16 to 22 June have also been critically examined. The following salient features are revealed in this study: (a) The southerly component in the wind direction and its depth increase as one moves wast of Long. 60°E southerly jet speed winds even being noticed near 40°E between about 850 and 700mb. (b) The high humidities are noticed in the western Indian Ocean west of 50°E upto about 500 mb, indicating considerable transport of moisture across the equator over this area. (c) An area of maximum dryness in levels above about 850 mb is noticed near Long. 60°E compared to other longitudes to the east and west. The difluence at the we3tern end (near 60°E) of the equatorial trough may also, to some extent, be responsible for relatively greater dryness at that longitude in levels above about.850 mb. (d) The inverions or isothermal conditions seen in some of the tephigrams would not appear to be due to any mass subsidence over the equatorial area, but mainly due to the presence of district airmasses, as is evident from the variations of specific humidity values and the lapse rates. (e) There would not appear presence of a deep layer of westerlies at all the longitudes over the equator. (f) The upper level easterlies would appear to begin at lower heights over the eastern regions than over the western regions of the equator, the jet speeds occurring near about 150 mb. (g) As at result of difference in circulation round 'highs' and 'lows' in the two hemispheres, it is difficult to trace systematic movements of pressure systems over the equator either from east to west or from west to east. From the present study, it would appear that for a proper understanding of transport of air and moisture across the equator in the western Indian Ocean and the adjoining land areas, it is necessary to have rawin and radiosonde observations at intervals of about 1 degree between Long. 37° and 45°E. Such observations alone will enable us to understand the characteristics of southwest monsoon current over the Arabian Sea and predictions of its activity over the west coast of India in terms of rainfall.